PTU-105 Cytoreductive Surgery and Small Bowel Transplantation is A Feasible Option for Patients with End-Stage Pseudomyxoma Peritonei. (17th August 2016) - Allan, P; Reddy, S; Moran, B; Vrakas, G; Giele, H; Mohamad, F; Gilbert, J; Sinha, S; Vaidya, A; Cecil, T; Friend, P
Abstract : Introduction: Pseudomyxoma peritoneii (PMP) arising from a low grade appendix tumour has good outcomes from cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. In those that recur or present with extensive small bowel involvement preventing complete tumour removal, obstruction leads to poor quality of life and is eventually fatal. Small bowel transplant could offer a life prolonging opportunity in endstage disease. Methods: From 2013–2015, 4 PMP patients were referred for consideration of small bowel transplantation with end stage disease and intestinal failure. Outcomes include time on PN, mortality, rejection, nutritional status, tumour markers, radiological evidence of recurrence and quality of life. Results: All 4 patients underwent radical debulking and small bowel transplantation. Average time on waiting list was 40 days (range 2–112). Organs transplanted: all were modified multivisceral transplants including stomach, duodenum-pancreatic complex, small bowel and abdominal wall; 3 received colon and 1 case a kidney. Median cold ischaemia time was 6hrs 59 mins (range 5hr 46 to 10 hr 22, 3 cases). Post-op stay on ITU average 14.5 days (range 2–45). Time on PN postoperatively: median 31 (range 19–51). Mortality risk: 2 survived at time of review, 11 months and 7 months; 2 died (Day 26 and day 64) the first from anastomotic leak, GVHD with associated fungal and bacterial chest sepsis, the other died of GI bleed and anastomotic leak. No episodes of acute rejection of intestinal graft seen but a single episode of grade 1 skin rejection of abdominal wall graft at day 68 treated with methylprednisolone. QOL data using EQ5D: pre-transplant 3 patients gave a VAS average 30 (range 10–75). Post-transplant VAS median 75 (70–80) at 2–4 months. Both the surviving patients are independent of TPN and well at home. Conclusion: From this preliminary series, cytoreductive surgery followed by multi-visceral small bowel transplantation is technically feasible for endstage PMP. Furthermore, in those who survived, it is has been life transforming giving so far an extra 7–11 months independent of TPN and excellent QOL. The long term outcomes will determine the effectiveness of this procedure. Early referral might allow surgery in physiologically fit patients improving the outcomes. This major surgical intervention requires close collaboration between Peritoneal Malignancy & Transplant teams. Disclosure of Interest: None Declared